2020
DOI: 10.1016/j.jpsychores.2020.110270
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of PTSD symptoms among medical assistance workers during the COVID-19 pandemic

Abstract: Background The outbreak of COVID 19in December 2019 spread quickly and overwhelmed the local healthcare system of the epicenter. A total of 346 medical assistance teams with 42,600 reserve medics were mobilized from around the country for emergency assistance. This study aims to examine the incidence of mental health symptoms and predictors of Post-Traumatic Stress Disorders (PTSD) symptoms among the reserve medics working in Wuhan, the capital city of Hubei Province. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 29 publications
8
51
0
2
Order By: Relevance
“…32 , 35 38 Physicians specifically who treat COVID-19 patients in Turkey, 39 , 40 China, 1 and Pakistan 41 are similarly experiencing an increase in depression and anxiety symptoms. Furthermore, healthcare workers in Italy 42 and China 43 who treated patients with COVID-19 experienced an increase in PTSD symptomatology, with similar findings to our data.…”
Section: Discussionsupporting
confidence: 90%
“…32 , 35 38 Physicians specifically who treat COVID-19 patients in Turkey, 39 , 40 China, 1 and Pakistan 41 are similarly experiencing an increase in depression and anxiety symptoms. Furthermore, healthcare workers in Italy 42 and China 43 who treated patients with COVID-19 experienced an increase in PTSD symptomatology, with similar findings to our data.…”
Section: Discussionsupporting
confidence: 90%
“…Receiving direct social support from friends, family, colleagues and supervisors was a key protective factor in all of the 19 studies that examined its association with psychological distress ( Table 2 ). For example, in HCW during the COVID-19 outbreak, higher levels of social support were associated with significantly lower levels of stress, depression, anxiety, depression and PTSD ( 28 , 31 , 38 , 62 , 70 , 78 , 88 , 90 , 94 , 102 , 139 , 156 ). These findings were consistent with that of a study of frontline medical staff during the COVID-19 outbreak who reported that a positive attitude from co-workers was important for reducing their distress ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…In nurses working during the SARS outbreak in Canada, higher perceived organizational support in the form of receiving positive performance feedback from doctors and co-workers, was associated with lower perceptions of SARS-related threat and reduced feelings of emotional exhaustion ( 59 ). Similarly, nurses, physicians, and HCW working during the MERS, COVID-19, and SARS outbreaks who perceived support from their supervisors and colleagues, experienced better mental health in the form of lower PTSD symptoms, lower distress, and being less likely to develop psychiatric symptoms, respectively ( 24 , 28 , 41 , 54 , 59 , 70 , 79 , 80 , 88 , 99 , 116 ).…”
Section: Resultsmentioning
confidence: 99%
“…The IES-R has been validated in COVID-19 studies in China [ 30 , 31 ]. We calculated a COVID-19-related PTSS/PTSD composite score (Cronbach’s α = 0.97) with the cut-off score being 24 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%